First results of LHCD experiments with 4.6 GHz system toward steady-state plasma in EAST. (12th November 2015) - Liu, F.K.; Ding, B.J.; Li, J.G.; Wan, B.N.; Shan, J.F.; Wang, M.; Liu, L.; Zhao, L.M.; Li, M.H.; Li, Y.C.; Yang, Y.; Wu, Z.G.; et al.
Abstract: A 4.6 GHz lower-hybrid current drive (LHCD) system has been firstly commissioned in EAST in the 2014 campaign. The first LHCD results with 4.6 GHz show that LHW can be coupled to plasma with a low reflection coefficient, drive plasma current and plasma rotation, modify the plasma current profile, and heat plasma effectively. By means of configuration optimization and local gas puffing near the LHW antenna, good LHW–plasma coupling with a reflection coefficient less than 5% is obtained. The maximum LHW power coupled to plasma is up to 3.5 MW. The current drive (CD) efficiency is up to 1.1 × 10 19 A m −2 W −1 and the central electron temperature is above 4 keV, suggesting that LH power could be mainly deposited in the core region, which is in agreement with code simulation. Experiments show that the current profile is effectively modified and toroidal rotation in the co-current direction is driven by the LHCD. Also, the CD efficiency and current profile depend on the launched wave spectrum, suggesting the possibility of controlling the current profile by changing the phase difference. Repeatable H-mode plasma is obtained by either the 4.6 GHz LHCD system alone, or together with a 2.45 GHz LHCD system, the NBI (neutral beam injection) system. The different ELM features of H-mode between the different heating methods are under investigation.